Buildings, Lands, and Rents: Understanding the Process and Impact of Monastic Suppression in Spain - Congost, Rosa (Religions, 2024)
In Ancien Régime Spain, ecclesiastical wealth consisted of not only land, but also the rental income raised from tenancies of which the Church was proprietor. Therefore, the suppression of monasteries and convents in Spain cannot be studied only in terms of the transfer of their principal estates. The incoming Liberal State appropriated the Church’s rents for its own use, although many had fallen into abeyance before the suppressions began. To assess the true impact of ecclesiastical confiscation, it is necessary to consider how far developments in religious sensibility, whether or not associated with new conceptions of property, before and after the liberal revolution, may have affected the treatment of these rents. In this article, I aim to examine the geographical distribution of the different property rights of the regular clergy in Spain under the Ancien Régime and to observe the role of the Liberal State in their evolution and in the fate of monastery and convent buildings. We will see, in all cases, the significant roles of the payers and receivers of different types of rents. Thus, territories with the same legal regime and similar institutions passed through the process in very different ways.